Bentuk Dan Tujuan Dalam Pelayanan Kunjungan Pastoral - Jesica Cindini Br Sembiring; Intansakti Pius X (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The Church is an institution that represents God in the world who has duties and services to the people. These ministries are given by the church to the congregation as pastoral duties in the world. By making pastoral visits, an ecclesiastical activity is to give attention and share love to Catholics in each environment of the parish or station by visiting Catholic family homes to help families solve their problems, giving repentance to family members who do not know the church to always be active in participating in ecclesiastical activities. The forms of service are divided into 2 types, namely counseling and visitation services. Usually church leaders and all church administrators make visits. This research uses the literature study method. In this study, scientific data sources are in accordance with the topic of discussion. First of all, it is necessary to discuss the meaning of pastoral visitation. Then whatever.